Effects of foundation species above and below tree line. (4th July 2017) - Gavilán, R. G.; Callaway, R. M.
Abstract: The facilitative effects of "foundation species" on community diversity and composition in alpine systems can be strong, but the strength of these effects often varies along gradients that occur above tree line. Here, we explore the effects of foundation species above and below tree line, a globally consistent and often abrupt climatic and ecological transition. The experiment was developed in Northern Rocky Mountains of Wyoming and Montana, USA, in vegetation with similar herbaceous physiognomies without trees, but containing dominant foundation species with "cushion" morphologies. In these systems, we compared the diversity and structure of plant communities occurring within these foundation species to that in the open at three sites below tree line and three sites above tree line. Above tree line, 69–94% of all species were significantly spatially associated with foundation species, whereas below tree line, 29–62% of the species were associated with foundation species. Similar patterns were observed in species accumulation curves with foundation species affecting the accumulation of species by +17 to +47% above tree line vs. –27 to +24% below tree line. Our results were consistent with the idea that facilitative interactions are more common with greater abiotic stress. However, our results also suggest the possibility that the climatic transition representing tree line might also represent a threshold, rather than a simple linear response, in how foundation species affect community diversity. A much larger sample size is warranted to thoroughly test such thresholds, but the fundamental ecological and physiological transition that plants experience at the climate of the tree line may also be reflected in small-scale species interactions that organize communities.